Pengaruh Inovasi Produk Terhadap Kinerja Keuangan dan Profitabilitas Industri Plastik Daur Ulang - , Maksalmina; Rahmah Yulianti; , Maryam; Rita Nengsih; Raisa Alifia (Jurnal Serambi Engineering, 2025)
This study is a literature review that examines the impact of product innovation on financial performance and profitability in the recycled plastic industry in Indonesia. With growing environmental awareness and the adoption of circular economy practices, the industry faces challenges to remain both competitive and sustainable. The literature review and previous studies indicate that product innovation significantly improves profit margins, asset turnover, and sales growth. Innovations in aesthetic design, functional features, and the use of environmentally friendly materials have been shown to increase consumer appeal and drive long-term profitability. In addition, structured innovation risk management and alignment with market trends are key to success. The study concludes that product innovation, combined with digitalization and sustainable approaches, is not only a strategic imperative, but also a fundamental pillar for the development of a resilient, competitive and environmentally responsible recycled plastics industry.